Uropathogens and antimicrobial susceptibility profiles of asymptomatic bacteriuria among pregnant women receiving antenatal care in traditional birth attendants homes in Ikono, Akwa- Ibom State, Nigeria - Umoyen, Anthony John; Akpan, Nseobong Godwin; Sunday, Cecilia James; Ekpenyng, Blessing Bassey (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Asymptomatic bacteriuria (ASB) in pregnancy is associated with adverse maternal and obstetric outcomes if untreated. The aim of this study was to determine the prevalence and susceptibility profile of ASB among pregnant women attending antenatal clinics in traditional birth attendant homes in Ikono, Akwa-Ibom State. Methods: The study was a cross sectional survey using 350 pregnant women with ASB. Mid-stream clean catch urine samples were collected from the women using sterile containers. The urine samples were cultured, bacterial colonies were identified and antibiotic sensitivity was done. Data was analyzed using SPSS version 20.0 and significant was set at ≤0.05. Results: The overall prevalence was 33.4% using 350 asymptomatic pregnant women. The mean age was 26.21±3.6 years and aged 27-32 have the highest prevalence (13.4) of ASB. 55.1% attained primary school, while 33.4% had informal education, monoparous (54%), 3rd trimester was 44.6% with 15.8% positive cases. Multigravidae was 71.1% with 19.4% positive cases. There was significant association of age, education, parity, occupation, monthly income, etc with ASB. The most common isolates were Escherichia coli (29.9%), then Klebsiella pneumonia (19.7%). Pseudomonas aeruginosa was susceptible to gentamicin (92%), Ciprofloxacin (83%) imipenam (83%) and azetronam (75%), while Staphylococcus saprophyticus was susceptible to imipenam (90%), then gentamicin at 80%. Multi-drug resistant were widespread in most of the isolates. Conclusions: Multi-drug resistant were observed in most of the isolates. Continuous and collaborative surveillance of ASB and antimicrobial resistance pattern are essential to reduce the consequence of asymptomatic bacteriuria in pregnant women.